Environmental Education: Role of Physical Environment in Students’ Learning in Gilgit-Baltistan, Pakistan - Alam, Sultan (Journal of Education and Vocational Research, 2017)
This study describes an action research report carried out in one of the community-managed schools in Gilgit-Baltistan of Pakistan. The purpose of the study is to explore the effects of the activities to create environmental awareness by paying prime focus on physical environmental conditions. It was observed that school-based smaller activities show a greater change among students, teachers and community members. These include celebration of environmental day, plantation day; quiz competitions, sharing information through notice boards and awareness campaigns to adjacent communities. These smaller activities helped them to realize the importance of environmental education particularly in learning process. The attitudinal change among students, teachers and community members was quite evident. They have shown a natural attachment with the school and its surrounding. Since the success and sustainability of such small-scale interventions are directly associated with active involvement of all the stakeholders of a school community, therefore, the study recommends that this important aspect must be given considerate attention to further augment the natural environment and to maximize the learning processes in schools.